(3ZGjI GdegQI aj GdRjGOI Ydi GdYTQIs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , (B833 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd CHh GdNjQ eMeO Hf eMeO Hf eMeO GdTgjQ HGHf GdLRQj CdG bO MeOJ Gddg aj Gdbhd ChdG EdgG YdjeG bGOQG eJaVdG (B- (3hCQOaJ MeOj KGfjG heUdjG Ydi GdeUWai eY ef baGg hef JdG (B-s
(3BNQgG (B:s
(3haj LfI GdYQaGf JMjj bdhHfG hJfRdgG QhV GdQVi eJbHdG (B- (3hUd Ydi GdgGOj GdHTjQ eMeO fHjc NjQ GdNdb WQG hCaVdG hBdg dg hGdUMH eG ZQHJ PcG hfGOi efGO HGdadGM eMjYdGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 45s
(3eYLe GdeDdajf (B3 / 687s
(3cTa GdXfhf (B2 / 1194s
(3TPQGJ GdPgH (B7 / 204s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs